Toxic shock and mortality in a dialysis patient - Mahmood, Akbar; Muhammad Imran; Balkhair, Abdullah (International Journal of Endorsing Health Science Research, 2018)
Background: Staphylococcus and Streptococcal infections are a matter of serious concern in the dialysis population especially those having tunnel catheter access. Importance of these organisms is their virulent nature, higher incidence and prevalence in tunnel catheters resulting in significant morbidity and mortality. Staphylococcal toxic shock syndrome (STSS) is an uncommon but potentially fatal disease with multisystem involvement. This is a case of toxin-producing methicillin sensitive staph aureus (MSSA) which is known to have high mortality. A high degree of clinical suspicion and prompt management is necessary to avoid fatality. The aim of the study was to get the idea for the management of the toxic shock in terms of reducing the morbidity and mortality rate. Case presentation: This case progressed to state of shock within few hours of presentation to emergency room and admission, attributed to be toxic shock with multi-organ failure. Management and Results: In the management of the patient at the very beginning, the infected catheter was removed further aggressive resuscitation and empirical antibiotics were administered but this case resulted into a fatality. Conclusion: The early action for source removal of the infection, appropriate antibiotic therapy and adjuvant therapy including clindamycin and immunoglobulin can effectively treat the toxic shock and its related complications.